Analysis of Translation Shift in Reclaim Your Heart (English-Indonesian Translation) - Frihatmawati, Rizky; Dhini, Ulfa Rahma; Rentiana, Leny Hikmah; Yasin, Achmad (EXCELLENCE: Journal of English and English Education, 2025)
Translation requires changing the forms of SL to reach the naturalness of TL, which frequently results in a shift. Shift or transposition is a crucial translation element, as providing the text with a good equivalent in the target language is not always feasible. This research aims to identify translation unit shifts and determine the aspects influencing each shift. The unit shift theory applied in this study is based on J.C. Catford’s translation shift theory. The aspects that cause or influence each unit shift in the unit analysis are based on Mildred L. Larson’s theory. This research was conducted as a descriptive qualitative study. The study focuses on the words, phrases, and sentences in Reclaim Your Heart and their translations that change during translation. The writer analysed the data to identify the unit shift from the source text to the target text. The shift patterns are determined following the unit categorisation. The observed patterns of unit shift in the translation of Reclaim Your Heart to Rebut Kembali Hatimu include shifts from morpheme to word, word to phrase, phrase to word, sentence to phrase, and sentence to clause. The factors that influenced translation and caused the unit shift occur because there are some aspects of language: lexical and grammatical.